KEABSAHAN DIREKTUR PERUSAHAAN PAILIT YANG MENJADI DIREKTUR PERUSAHAAN LAIN - Imam Rahmat Feisal (RechtIdee, 2019)
This journal entitled "Validity of the Director of Corporate Bankruptcy The Become Director of Companies", originating from legal conflict that occurs between the requirements to become directors that requires not been declared bankrupt under Article 93 of Law Number 40 Year 2007 regarding Limited Liability Company with the consequent bankruptcy the only limit debtors to manage and master the wealth contained in Article 24 paragraph (1) of Law No. 37 of 2004 on Bankruptcy and Debt Payment Obligation, the formulation of the problem: 1. Why did the director of the bankrupt company can not be a director in another company ? 2. What legal remedies for directors at the company bankrupt in order to become a director in another company?. Normative methods underlying the writing of this, with statute approach, conceptual approach, and case approach.This study stems from obscurity as a result of bankruptcy, especially regarding the rights of the insolvent company directors can not be a director in another company within a period of 5 (five) years after being declared bankrupt.This study suggests that the terms barring a bankruptcy of directors to become directors in the company of other conflicts with settings that declare bankruptcy as a result of the bankruptcy of a ruling not only on wealth alone. It is also contrary to the basic concept of civil rights. Legal effort to do ever declared bankrupt directors to become directors of the company other is to conduct a tort lawsuit to the notary and the Ministry of Justice and Human Rights. Ministry of Justice and Human Rights can be sued also in the State Administrative Court because it is not in accordance with the General Principles of Good Governance.